TANTANGAN PERKEBUNAN KELAPA SAWIT SWADAYA ASOSIASI MANDIRI DI DESA SUNGAI BULUH DALAM MEMENUHI STANDAR SERTIFIKASI RSPO - Gabriel Aleksander; Sakti Hutabarat; Eliza Eliza (PEKBIS, 2019)
The expansion of palm oil plantations has not only had a positive impact but alsovarious negative impacts. International markets require the management andprocessing of palm oil plantations to be responsible by taking account ofenvironmental, social, and economic aspects. Palm oil produced must be asustainable product (sustainable) to be accepted in the international market. Thisthen spawned a concept of sustainable palm oil by a body called the Roundtable onSustainable Palm Oil (RSPO). The purpose of this study was to analyze the gapbetween the RSPO criteria standards and the practices of planters, analyze thecapabilities and challenges of Independent smallholders to obtain RSPOcertification. This research uses descriptive analysis. The results of the researchindicate that best practices or application of RSPO principles to independentSmallholders palm oil planters has reached 75%, from 138 indicators there are 13indicators that become findings, from 13 indicators findings there are 5 majorindicators. Asosiasi Mandiri ability to be able to obtain RSPO certification ie (1)Planters Association has been well organized (2) have understanding or awarenessof the importance of RSPO certification objectives (3) has fulfilled the 6 principles ofthe 8 principles of the RSPO P & C standard (4) supported by non-governmentalorganizations, and challenges faced by (1) generally low levels of plantationeducation (2) Principles 4 and 5 that have not met the RSPO P & C standards (3)associations require substantial fees for RSPO certification. To complete the fivemajor indicators, the Association requires training or assistance in recording eachcultivation activity especially on the use of pesticides, training and the formation of ateam of spray units (TUS) and empowered in any plantation maintenance activities,manufacture of special warehouses for pesticide storage and create special disposalsites or looking for distributors of processing or recycling of pesticide waste, andconducting annual medical monitoring programs specific to pesticide operators.